2023
DOI: 10.3390/biomedicines11102819
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Ferritin–Lymphocyte Ratio in COVID-19

Alexander Liu,
Robert Hammond,
Kenneth Chan
et al.

Abstract: Introduction: The ferritin–lymphocyte ratio (FLR) is a novel inflammatory biomarker for the assessment of acute COVID-19 patients. However, the prognostic value of FLR for predicting adverse clinical outcomes in COVID-19 remains unclear, which hinders its clinical translation. Methods: We characterised the prognostic value of FLR in COVID-19 patients, as compared to established inflammatory markers. Results: In 217 study patients (69 years [IQR: 55–82]; 60% males), FLR was weakly correlated with CRP (R = 0.108… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…Liu et al determined that the ferritin/lymphocyte ratio (FLR) holds prognostic significance in COVID-19 patients and is distinct from other inflammatory markers like C-reactive protein (CRP) and white cell count (WCC). FLR shows a high degree of sensitivity and negative predictive values for predicting adverse clinical outcomes in COVID-19, suggesting it could serve effectively as a "rule-out" test [35]. Consistent with these findings [34], our study found that the FL index was significantly elevated in patients who did not survive the infection compared to those who recovered.…”
Section: Discussionsupporting
confidence: 85%
“…Liu et al determined that the ferritin/lymphocyte ratio (FLR) holds prognostic significance in COVID-19 patients and is distinct from other inflammatory markers like C-reactive protein (CRP) and white cell count (WCC). FLR shows a high degree of sensitivity and negative predictive values for predicting adverse clinical outcomes in COVID-19, suggesting it could serve effectively as a "rule-out" test [35]. Consistent with these findings [34], our study found that the FL index was significantly elevated in patients who did not survive the infection compared to those who recovered.…”
Section: Discussionsupporting
confidence: 85%